Harmonisation, déréglementation et mise en réseau : quelques clés pour l’avenir - Bouchard, Jean (Assurances)

(untitled) (HEC Montréal, 1993)
During the last decade, the Canadian financial sector has experienced unprecedented modifications and readjustments. Today, this transformation continues and the 1990s offers many challenges. The author first comments on the BAC's analysis of the Policy Paper delivered by Minister Robic, in March 1993. He agrees with the efforts Quebec is making to modernize its legislation. He insists on a few points of interest which are to provide a greater efficiency of the financial sector: the harmonization and coherence between federal and provincial legislations and regulations; the advantages of networking between financial sectors; and the advantages such an orientation will bring to the consumer.